THE HISTORY OF THE EMERGENCE OF INFORMATION TECHNOSOLOGIES - Usmonov Murod Sadikovich (Web of Journals Publishing, 2025)
By the concept of information and Communication Technology (ICT), we understand the combination of methods, tools and techniques for searching, storing, processing, presenting and transmitting graphic, text, digital, audio and video data based on personal computers, computer networks and communications.